A prospective policy transfer of learning from abroad in funding long-term care in England. Issue 1 (20th July 2021) - Powell, Martin
Abstract : Purpose: This article explores to what extent the long debate in England over the funding of long-term care (LTC) has involved learning from abroad. Design/methodology/approach: It draws on Mossberger and Wolman's (2003) framework which proposes criteria for assessing policy transfer as a form of prospective policy evaluation: awareness; assessment and application. The documents examined are the sources cited by the reports that examined funding LTC in England since 1999. The study uses interpretive content analysis in a deductive approach (applying the framework) that focuses on both manifest and latent content. Findings: It finds that both the reports and the cited studies tend to focus on a fairly narrow range of nations, with most attention on Germany, Japan and Scotland. Most studies broadly do not provide much in the way of a clear rationale, and the level of details provided varies. There is relatively little focus on problems. Aims, objectives and goals are little mentioned in some studies, but they tend to be fairly abstract or "high level." Similarly, there is limited detail on settings. Finally, only a few studies provide a clear recommendation. Originality/value: It focuses on the neglected topic of the evidence behind reports which are intended to provide recommendations for policy change. The Mossberger and Wolman's (2003) framework has been used in a small-scale but appears to be well-suited for this purpose.